Social Media Utilisation in Increasing Sales at UMKM Kube Wanita Pamulang Estate - Silviyani, Yuli Anita; Fitriyah, Fitriyah; Risthi, Alyssa (Transpublika Publisher, 2025)
Micro, Small and Medium Enterprise (MSME) sector has various problems such as decreased sales, capital, hampered distribution, difficulties with raw materials. MSME players must also make changes to their marketing orientation, especially in the current modern era. Many small business owners are transitioning to online commerce in order to boost sales, however, they often lack the technological know-how to do so effectively. This initiative is designed to offer knowledge and expertise to female entrepreneurs in Pamulang Estate on utilizing social media for marketing and sales, as well as guidance on using online marketplaces to sell products. Additionally, it involves analysing how social media can be used to attract customers and expand consumer base. As a result of this project, partners will gain a better understanding of marketing and promoting products independently through social media.